2006
DOI: 10.1001/archpsyc.63.4.356
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Relational Memory Deficits in Schizophrenia

Abstract: Schizophrenia is characterized by a specific deficit of relational memory, which is associated with impaired function of the parietal cortex and hippocampus. Abnormal relational memory may be at the core of 2 prominent features of schizophrenia, ie, cognitive deficits and psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
75
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 72 publications
(93 reference statements)
13
75
2
Order By: Relevance
“…The hippocampus is dysfunctional in schizophrenia (Weiss, 2003; Ongür, 2006; Ragland, 2001; Ledoux, 2013; Heckers, and Konradi, 2010). Meta-analyses have concluded that schizophrenia is associated with memory impairment (Heinrichs, and Zakzanis, 1998; Aleman, 1999) and that hippocampal recruitment is impaired during the performance of memory tasks (Weiss, 2003; Heckers, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus is dysfunctional in schizophrenia (Weiss, 2003; Ongür, 2006; Ragland, 2001; Ledoux, 2013; Heckers, and Konradi, 2010). Meta-analyses have concluded that schizophrenia is associated with memory impairment (Heinrichs, and Zakzanis, 1998; Aleman, 1999) and that hippocampal recruitment is impaired during the performance of memory tasks (Weiss, 2003; Heckers, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have attempted to use relational mnemonic tasks, which are specific to hippocampus, to assess hippocampal function in schizophrenia (Coleman et al, 2010; Öngür et al, 2006; Hanlon et al, 2005, 2006; Titone et al, 2004). One of these tasks is the transverse patterning (TP) problem, which involves a completely overlapping set of relationships among stimuli.…”
Section: (1) Introductionmentioning
confidence: 99%
“…Considerable evidence suggests that individuals with schizophrenia display subtle, but consistent, memory impairments [1, 2]. However, individuals with schizophrenia are not impaired on all forms of memory [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with schizophrenia are not impaired on all forms of memory [1, 3]. Furthermore, the effect of treatment on memory impairments in schizophrenia remains poorly understood at both the cognitive and neurobiological levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation